EDUKASI PERAWATAN KAKI MELALUI MEDIA GUIDANCE MOTION PICTURE DAN LEAFLET TERHADAP PERILAKU PERAWATAN KAKI NON ULKUS PADA PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS LOCERET - Yeni Setyorini; Yulis Setiya Dewi; Laily Hidayati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: Diabetes mellitus’s with high blood glucose level is at a risk to get ulcus diabeticum because do not do the foot care. The aimed of this research was to examine effectivity of foot care education by guidance motion picture and leaflet media in Diabetes mellitus type 2’s behavior in Puskesmas Loceret.Methods: This research was using quasy-experiment with pretest-posttest control group design. The population were Diabetes mellitus type 2’s at Puskesmas Loceret working area. This research used 3 group, they were treatment group (guidance motion picture+leaflet), positive control group 1 (guidance motion picture), and positive control group 2 (leaflet), each group consisted of 10 respondents taken according to purposive sampling from January-March 2014. Data were collected using questionnaire and observation and then analyzed using Wilcoxon signed rank test and Kruskal-Wallis test with level of significance <0.05.Result: Results showed that increasing knowledge is significant for treatment group (p=0.005), the positive control group 1 (p=0.011), the positive control group 2 (p=0.097). Analysis of attitude for all group (p=0.005). Analysis of action for treatment group (p=0.005), positive control group 1 (p=0.006), the positive control group 2 (p=0.011). There are different effectivity between guidance motion picture+leaflet combination, guidance motion picture, and leaflet in increasing knowledge (p=0.047), attitude (0.022), and action (p=0.037).Discussion: It can be concluded that education with guidance motion picture+leaflet combination, guidance motion picture, and leaflet media influence non ulcus foot care behavior, but for leaflet, it does not influence their knowledge. So, nurses can use one of that media to get effective influence when giving health education to Diabetes mellitus type 2’s. Further research should evaluate other factors of knowledge, attitude, and action also do direct observation of action to gain more accurate data.